Desain Primer PCR Sebagai Biomarker COVID-19 Strain Terbaru Yang Di Identifikasi Di Januari 2021 - Herli, Muhammad Azhari; Hari, Dewi Gulyla; Rahmawati, Ayu (Photon: Jurnal Sain dan Kesehatan, 2021)
Coronavirus disease 2019 (COVID-19) is a contagious disease caused by Severe Acute Respiratory Syndrome Corona Virus 2 (SARS CoV-2). The disease first spread in Wuhan, Hubei Province, China in December 2019. SARS-CoV-2 is highly contagious and has grown rapidly around the world since its discovery. Until January 2021, a total of 101,406,059 confirmed cases of SARS-CoV-2 infection worldwide with a death toll of 2,191,898 and still growing. Diagnosis of COVID-19 is carried out in two common ways, namely a rapid test and PCR (polymerase chain reaction). This study aims to design a PCR primer for the latest COVID-19 strain isolated in January 2021 with the insilico method (computer simulation) so that the primer used as a COVID-19 biomarker is fast and accurate. The results of this study obtained 10 of the best primers from the latest COVID-19 strains with codes MW454767, MW454771, MW460582, MW454660 which were identified on 11 Jan 2021.